(untitled) (JOURNAL OF ADVANCES IN LINGUISTICS, 2014)
Many humans value our environment. We must value our environment to protectit from depleting, because of uncertainty of how we live is very much different from our past values. To project or forecast the human consequences of global, we need to knowthe future state of the natural environment,the future of social and economic organization,the values held by the members of future social groups,the proximate effects of global change on those values, andthe responses that humans will have made in anticipation of global change or in response to ongoing global change.